(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Many people are fond of drinking teas with different flavors and combinations. Nowadays, people are more adventurous and love to try a new taste and experiment with new flavors. They adore everything new, exciting, and beneficial to them. Therefore, the researchers created an idea of offering different flavors of hot and cold milk teas that are suitable to their needs and wants, especially in terms of taste. It has many beneficial effects on health, that is, it increases blood flows and reduces disease. Four Tea is a milk tea shop that offers hot and cold milk teas. It is being conceptualized when fourth-year business students were planning to build their business. “Four Tea” is a term that refers to four students, combined with “tea” for the customers to know that the business is a milk tea shop. This research was conducted to determine the extent to which the goods or services that can be generated by the business are needed or demanded and to design the appropriate marketing strategies and plans to ensure that business outputs will reach and can be accepted by the target market. The researchers conducted a survey consisting of male and female respondents. The survey was conducted in 98 Maginhawa St., Diliman, Quezon City. It consisted of 50 survey questionnaires that were given to 50 respondents. A total of 33 respondents were female (66%), and male respondents accounted for 17 individuals (33%). Therefore, the researchers found out that female respondents were more likely to answer survey questionnaires than males. The result of this study can help in improving the business, such as in pricing the products offered that can be feedback of the customer. Although the business will offer good service and superior quality products, the business must have stable offering good service and superior quality to acquire the adherence and contentment of the customers. The researchers will continue to develop and enhance its product and idea to satisfy the customers and loyalty will continuously study the business and products and services offered because nowadays most people prefer changes over time. The researchers will continue to operate and handle the business until it succeeded and become a well-known business.